Pendekatan Birokrasi dalam Pengambilan Keputusan untuk Kebijakan Luar Negeri - Asep Setiawan, Laode Muhamad Fathun (UIR Press, 2021)
Bureaucratic politics model in foreign policy analysis focuses on the role played by many bureaucrats in foreign policy making process. The argument for this approach is foreign policy making process and its implementation by government rely on their bureaucrats. The bureaucratic politics approach asserts that foreign policy is mainly formulated by the bureaucrats rather that by the key decision makers. However role of bureaucrats should not be exaggerated since leaders and key decisions makers select their advisor and the advice they want to hear should confirm their own views.